Comparison between ozone and CHX gel application for reduction of pain and incidence of dry socket after lower third molar removal - Jehona Ahmedi; Zana Agani; Resmije Ademi Abdyli; Mergime Prekazi Loxha; Vjosa Hamiti‐Krasniqi; Aida Rexhepi; David Stubljar (Wiley, 2023)
Abstract Objectives The aim of this study is to evaluate the efficacy between ozone gas and 1% chlorhexidine (CHX) gel in the incidence of dry socket after surgical extraction of impacted lower third molars. Material and Methods Overall, 30 patients of both genders were included in the study, with indication of surgical extraction of lower third molar, positioned similarly after being clinically and radiographically checked by X‐ray and orthopantomography. Each patient was subjected to both groups in separate sessions: treated with ozone gas and with CHX gel 1%. Data on pain intensity, number of taken analgesics‐painkillers, and dry socket were recorded for 48 h and at Day 7. Results Ozone gas and CHX gel effectively reduced pain intensity and prevented dry socket. The number of taken analgesics 48 h and 7 days after surgery showed no statistical significance. The same was observed for the distribution of pain. Only one patient reported the occurrence of dry socket 7 days after the surgical extraction. Conclusions Ozone gas and CHX 1% gel are both efficient in decreasing postoperative symptoms and incidence rates of dry socket, but in comparison to each other, the use of ozone gas is showing a bit better prevention capability.